Study of the traditional tabique constructions in the Alto Tâmega region - Pinto, J. (2012)
Tabique constructions can be found almost everywhere in Portugal. In fact, it is one of the most used traditional building techniques using raw materials, such as earth and wood, particularly for interior partition walls. A tabique constructive element can be described as a timber structure, more or less complex and robust, filled and plastered in both sides by a composite earth based material. Trás-os-Montes e Alto Douro region is the northeast region of Portugal where the tabique heritage is very vast/the most significant. Tabique can be found in any kind of constructions, from the very simple rural dwellings to more important buildings and constructions, such as castles, villas, etc. Many of the existing tabique constructions present an advanced stage of deterioration, partially justified by the maintenance knowledge and practice that has been lost over time about these techniques and their rehabilitation procedures, due to the fast introduction of new materials in the construction. Considering this, research work has been developed with the main objectives of studying the building process of tabique construction elements, typifying dimensions of tabique walls and its components, and characterizing constitutive materials. Within this research project, it was intended to create a knowledge basis that can guide and stimulate future rehabilitation actions in this field. At the first stage, this study was developed at one of the six council associations of the Trás-os-Montes e Alto Douro region, namely the Alto Tâmega. A selected group of constructions, representative of the existing heritage in the region, were detailed studied. The results of their characterization can help to recuperate/recover the practice knowledge concerning this traditional eco-construction technique, supporting the rehabilitation of the existing construction heritage, but also its eventual application in new construction.